Meningkatkan Hasil Belajar Menggunakan Media Diorama Pada Pembelajaran Ipa Materi Ekosistem Untuk Siswa Kelas V Sdk Ora Et Labora Pamulang Tahun Pelajaran 2021/2022 - Haryatmo, Imanuel Sigit; Martanto, FX Belly (Al Makki Publisher, 2025)
This research aims to improve student learning outcomes on ecosystem materials through the use of diorama media in grade V SDK Ora et Labora Pamulang for the 2021/2022 school year. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The use of diorama media is expected to increase students' understanding and interest in ecosystem materials, as well as improve their learning outcomes. The results of the study show that the use of diorama media can improve student learning outcomes, both in terms of understanding concepts and the application of ecosystem materials in daily life. Based on these findings, it is suggested that diorama media be used further as an alternative in science learning, especially for materials that require visualization to facilitate student understanding.